The effect of lifestyle and brand image On Customer’s Purchase Decision - Dewi, Sita; Ismail, Ismail; Listyowati, Dwi; Napitupulu, Bertha Elvy; Saragih, Kuncu; Hermawan, Francisca (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
In Indonesia, motorcycles are a popular transportation. Motorcycle users are numerous, with 85% of Indonesian households owning a motorcycle. The motorcycle industry in Indonesia is growing rapidly. Innovations in the motorbike industry are constantly taking place considering motorbike brands are becoming more and more competitive. Brands are becoming more focused in innovation and one of the ways they carry this out is by targeting a more segmented customer base. This is reflected in the variety of marketing strategies, including the variety of product design available in the market, variety of price range, up to the variety of advertisement channels and key opinion leaders used, making it in the best interest of brands to know the lifestyle of their customers to create a product that suits their needs. Brand image influences the perception of customers regarding how good or bad a product made by the brand is. By taking a case study of the Yamaha Nmax motorcycle customers in central Jakarta, this study aims to determine the effect of lifestyle and brand image on custumer’s purchase decision. With a sample of 100 customers, the results showed that lifestyle and brand image influence purchasing decision for Yamaha Nmax customers both partially and simultaneously.